Review article: I. Anderson, 'This Is Our Music: Free Jazz, the Sixties, and American Culture, S.Saul, Freedom Is, Freedom Ain’t: Jazz and the Making of the Sixties', I. Monson, 'Freedom Sounds: Civil Rights Call Out to Jazz and Africa' - Hersch, Charles (Jazz Research Journal, 2009)
Iain Anderson, This Is Our Music: Free Jazz, the Sixties, and American Culture. Philadelphia: University of Pennsylvania Press, 2007. Scott Saul, Freedom Is, Freedom Ain’t: Jazz and the Making of the Sixties. Cambridge, MA: Harvard University Press, 2003. Ingrid Monson, Freedom Sounds: Civil Rights Call Out to Jazz and Africa. Oxford: Oxford University Press, 2007.